1974
DOI: 10.1099/00222615-7-3-367
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocine-Like Activity of Group-A Streptococci Due to the Production of Peroxide

Abstract: PLATES XV AND XVIB A c T ER I o c I N ES represent a unique class of proteinaceous bactericidal substances that are produced by certain strains of bacteria and exhibit a narrow range of effectiveness against other strains of the same or closely related species (Nomura, 1967;Brandis and Smarda, 1971 ;Reeves, 1972). Besides those on which a great amount of work has been done, there are others that are still poorly characterised ; and there may even exist inhibitory phenomena that have mistakenly been attributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1975
1975
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Other lactic acid bacteria have been reported to accumulate H 2 O 2 in the culture medium (15,32). This accumulation has been attributed to various H 2 O 2 -producing enzymes, including pyruvate oxidase (25,43), H 2 O 2 -producing NADH oxidase (2,21,22), lactate oxidase (50), and ␣-glycerophosphate oxidase (39).…”
Section: S Pyogenes Contains a Single Nox Homologue But Lacks Nprmentioning
confidence: 99%
“…Other lactic acid bacteria have been reported to accumulate H 2 O 2 in the culture medium (15,32). This accumulation has been attributed to various H 2 O 2 -producing enzymes, including pyruvate oxidase (25,43), H 2 O 2 -producing NADH oxidase (2,21,22), lactate oxidase (50), and ␣-glycerophosphate oxidase (39).…”
Section: S Pyogenes Contains a Single Nox Homologue But Lacks Nprmentioning
confidence: 99%
“…Furthermore, in vitro studies have shown that GAS itself produces significant quantities of H 2 O 2, mainly by an enzymatic lactate oxidase activity (37). Even mM concentrations of this highly membrane-diffusible oxidant have been measured from the culture supernatants (14,22,30,37). GAS may therefore face H 2 O 2 at concentrations that are lethal to many catalase-positive bacteria.…”
mentioning
confidence: 99%
“…The inhibitory substances produced by our isolates have not been identified, but probably do not include hydrogen peroxide, since the strains were all grown anaerobically (LeBien and Bromel, 1975;Malke et al, 1974). Since L. mtrinus isolates produce large amounts of lactic acid , it would be reasonable to assume that this product accounts, at least in part, for inhibitory activities recorded with this species.…”
Section: Discussionmentioning
confidence: 90%
“…Many inhibitory microbial substances have been reported: ammonia (Rogul and Carr, 1972), lactic acid (Tramer, 1966), hydrogen peroxide (Donoghue and Tyler, 1975;Malke et al, 1974), organic fatty acids (Donoghue and Tyler, 1975;Walstad et al, 1974), hydrogen sulfide (Freter, 1976;Freter et al, 1983), antibiotics (Ducluzeau et al, 1976;Gilvez et al, 1986), and bacteriocins (Reeves, 1972;Tagg et al, 1976;LeBlanc et al, 1983). The inhibitory substances produced by our isolates have not been identified, but probably do not include hydrogen peroxide, since the strains were all grown anaerobically (LeBien and Bromel, 1975;Malke et al, 1974).…”
Section: Discussionmentioning
confidence: 95%